57 A Closed Loop Audit of Post-Operative Driving Advice Documentation. (12th October 2021) - Khan, H; Tang, C; Kamalakannan, B; Bamford, R
Abstract: Aim: The Driving and Vehicle Licensing Agency state post-operatively it is between the patient and doctor to establish when would be safe to resume driving, providing recovery does not exceed three months. This audit aimed to assess and improve the documentation rate of driving advice in the discharge summaries given to patients post abdominal surgery. Method: Retrospective data collection from electronic records over the months of August and September 2020. 132 discharge summaries were screened to assess the baseline rate of verbal/documented driving advice given on discharge. Following the 1st cycle, posters encouraging the inclusion of driving advice and demonstrating how to access driving advice to discharge summaries were developed and distributed across the surgical wards. A 2nd cycle re-audit was conducted in October 2020 to measure the effect of change, and a further 3rd cycle audit was conducted in November 2020. Results: 1st cycle included 132 patients. 62% had documented advice on their discharge summaries, while 38% had no proof of driving advice. After intervention, 2nd cycle included 30 patients. Results showed a significant increase in advice documentation (80%). A 3rd cycle was carried out with 47 patients. This showed a reduction in advice documentation (66%). Conclusions: Driving advice on discharge in post-operative patients is crucial part of patient safety. Implementation of intervention has increased the documentation of driving advice showing enhancing patient safety. However, 3rd cycle after registrar's changeover showed a decrease in the rate of documentation. A teaching session is planned for new doctors followed by 4th cycle.